2018
DOI: 10.1093/nop/npy033
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and prognostic factors of ataxia in children with posterior fossa tumors

Abstract: Background There is minimal literature specific to motor outcomes in children with posterior fossa tumors (PFTs) despite ataxia being a significant problem in this group. This study aims to report children’s physical outcomes following management of PFT and determine which factors affect severity of ataxia and functional limitations. Methods Forty-two children aged between 5 and 17 and between 1 and 4 years following surgery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
1
8
0
2
Order By: Relevance
“…Ataxia is often present in children pre-operatively (reported as evident in 60% of children in a meta-analysis by Wilne et al [68]). Ataxia is then thought to increase post-operatively with pCMS highlighted as a risk factor for both more severe [23] and long-term ataxias [29]. Specific tumor location is also noted to be a risk factor for long-term ataxia with involvement of the deep cerebellar nuclei, a predictor for problems over a year after surgery [29].…”
Section: Motor Disturbances In the Context Of Pcmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ataxia is often present in children pre-operatively (reported as evident in 60% of children in a meta-analysis by Wilne et al [68]). Ataxia is then thought to increase post-operatively with pCMS highlighted as a risk factor for both more severe [23] and long-term ataxias [29]. Specific tumor location is also noted to be a risk factor for long-term ataxia with involvement of the deep cerebellar nuclei, a predictor for problems over a year after surgery [29].…”
Section: Motor Disturbances In the Context Of Pcmsmentioning
confidence: 99%
“…Specific tumor location is also noted to be a risk factor for long-term ataxia with involvement of the deep cerebellar nuclei, a predictor for problems over a year after surgery [29]. Overall, there is a lack of understanding regarding the recovery potential for children with motor problems in conjunction with pCMS although recent studies suggest that children who were diagnosed with pCMS are likely to have more often long-term therapy needs [23,27].…”
Section: Motor Disturbances In the Context Of Pcmsmentioning
confidence: 99%
“…Высокая распространенность остеопенических состояний определяет актуальность и необходимость изучения данной проблемы с целью оптимизации ранней диагностики для предотвращения тяжелых осложнений в будущем. Учитывая, что у пациентов с опухолями головного мозга, особенно с локализацией в области задней черепной ямки и мозжечка, нередко наблюдается атаксия, проявляющаяся расстройствами поддержания равновесия и ходьбы, пошатыванием и нарушениями координации движений [ 29 ], в сочетании со сниженной МПК существенно увеличивается риск переломов даже в молодом возрасте.…”
Section: Discussionunclassified
“…Sønderkær et al [ 6 ] reported that ataxia may persist at 10 years after surgery. More recent reporting with standardised outcome measures has also observed approximately 70% [ 7 , 8 ] of children with PFT which demonstrate balance dysfunction more than 1 year following surgery.…”
Section: Introductionmentioning
confidence: 99%